The decrease in hippocampal transient receptor potential M2 (TRPM2) channel and muscarinic acetylcholine receptor 1 (CHRM1) is associated with memory loss in a surgical menopause rat model - Pala, Sehmus; Atilgan, Remzi; Kuloglu, Tuncay; Yalcin, Emre; Kaya, Nalan; Etem, Ebru (Termedia Publishing House Ltd, 2021)
Introduction: The aim of the study was to investigate the association of transient receptor potential M2 (TRPM2) channel and muscarinic acetylcholine receptor 1 (CHRM1) activity with the memorial functions that are deteriorated in surgical menopause. Material and methods: A total of 14 female rats were randomly divided into 2 groups: group (G)1: sham group; group (G)2: surgical menopause group, the group in which bilateral ovariectomy was performed. Fourteen days after the surgical procedure, learning and memorial tests were performed in G1 and G2 for a totally 13 days. The time required for the rats to find the cheese in the labyrinth was recorded and statistical evaluation of it was performed between groups. On the 14th day of the memory test, the rats were decapitated and the brain tissues were fixed in 10% formalin. Hippocampal TRPM2 and CHRM1 gene expression was evaluated with RNA isolation, complementary DNA (cDNA) synthesis and quantitative real-time PCR (qRT-PCR) analysis. TRPM2 and CHRM1 immunoreactivity was evaluated in hippocampal tissue with the immunohistochemical method. Histo-score was calculated regarding the diffuseness of and severity of the staining; and statistical analyses were performed. Results: In the ovariectomized group, the mean time required for the rats to find the cheese was statistically significantly elongated (39.29 +/- 4.0 s vs. 29.86 +/- 2.6 s). When the hippocampal TRPM2 and CHRM1 gene expression and immunoreactivity were compared with the sham group, there was a statistically significant decrease in the surgical menopause group (p < 0.05). Conclusions: In surgical menopause, in deterioration of memorial functions, hippocampal TRPM2 channel and CHRM1 activity plays an important role.
Keywords: surgical menopause; rat; trpm2; chrm1; memory